Nonlinear power control of variable speed wind turbines above rated wind speed. (2018) - Ma, Miaomiao; Sun, Yushen; Yu, Shaoyuan; Pan, Junjun
This paper proposes a triple-step nonlinear control scheme for variable speed wind turbines above the rated wind speed to maintain the output power at the rated value. The controller design procedure is divided into three parts: steadystate-like control; feedforward control based on reference dynamics; and state dependent feedback control. The gains of the controller are state-dependent and parameter-varying. The simulation results for a NREL-offshore-baseline 5 MW wind turbine system show the efficiency of the proposed nonlinear controller.